KEMBANG API - Laning, Billy Syalom; Ardini, Ni Wayan (MELODIOUS : JOURNAL OF MUSIC, 2024)
Fireworks work is a form of the cultivator's love for fireworks when the cultivator was small, when the cultivator was 5 years old the cultivator listened to the roar above the sky. When the cultivator comes out the cultivator sees a colorful light and rumbling sound that has a beauty felt by the cultivator, so that through an approach to liking, the cultivator wants to create a work of musical composition that the cultivator believes this work can Give a message or meaning to the beauty of fireworks.  This work takes the form of a percussion ensemble. Using the creation method used 1. Contemplation Through this process, the ensemble can reflect and construct ideas or ideas that will be embodied in a musical piece. 2. Exploration of the source of ideas: Seeking and collecting ideas and inspiration from various sources, such as everyday life, nature, and other music 3. Determination of musical concepts: Formulate concepts or themes that will be the foundation in the creation of ensemble music. 4. Music concept making: Composing a musical concept that contains ideas and inspiration that have been collected. 5. Ensemble music making: a touch of kolintang as pitched percussion as the melody color of this piece. The work of KEMBANG Api is divided into 3 parts: Part 1 where the cultivator tells about the awaited beginning when setting off fireworks with a tense atmosphere. Part 2 cultivators tell the scene when fireworks explode above the sky with a colorful atmosphere giving 5/4 difficulty. Part 3 tells the story of when the fireworks have finished exploding and the atmosphere returns to calm with percussion instruments. The cultivator hopes that his work can open up a space of reflex for listeners, inviting them to explore various beats in this work.